Estudio del equilibrio y cinética de adsorción de Cd(II), Ni(II) y Cr(VI) usando Quitosano y Quitosano modificado con cobre - Castro, S.; Cerda, R.; Betanco, N.; Canelo, F.; López, X.; García, A.; Benavente, M. (Nexo Revista Científica, 2014)
In this paper, the equilibrium and adsorption kinetics of Cr(VI), Cd(II) and Ni(II) onto Chitosan and Cu-chitosan was studied. Metal ion solutions at different initial concentration were put in contact with chitosan and Cu-chitosan and the mixture was agitated by 3 – 4 h. Afterwards, the samples were analyzed by atomic absorption spectroscopy. The experimental data of adsorption equilibrium were evaluated by application of Langmuir and Freundlich isotherms; while the kinetics experimental data were evaluated using kinetic models of pseudo-first order and pseudo-second order. The results showed that the metallic ions were effectively adsorbed by the chitosan (Cd and Ni) and Cu-chitosan (Cr). Besides, it was found that the experimental data of adsorption equilibrium of Cr(VI) and Ni(II) fit the Langmuir model, while the equilibrium adsorption data of Cd(II) were better fitted by Freundlich model. The maximum adsorption capacity of chromium (29.7 mg/g Cu-chitosan), cadmium (102.0 mg/g chitosan) and nickel (83.31 mg/g chitosan) was determined using the Langmuir model. The results of adsorption kinetics of the metallic ions showed that the experimental data were better adjusted by pseudo-second order model. Therefore, the rate-limiting step is the adsorption reaction and not mass transfer processes. DOI: http://dx.doi.org/10.5377/nexo.v26i2.1285 Nexo Revista Científica Vol. 26, No. 02, pp. 56-68/Diciembre 2013